Effectiveness of an Endotracheal Tube Adjustable Stabilizing Set to Prevent Unplanned Extubation in Preterm Infants: A Quasi-experimental Study. - Aungsumalin Sangngam; Jutamas Chotibang; Patcharee Woragidpoonpol (Pacific Rim International Journal of Nursing Research)
Preterm infants born before 34 weeks of gestation often face respiratory challenges and may require resuscitation with an endotracheal tube and ventilator support. Unplanned extubation is a common problem for such infants, affecting their care and outcomes. This quasi-experimental study compared the incidence of unplanned extubation, stability of vital signs and oxygen saturation between a control group (n = 24) receiving routine care in a neonatal intensive care unit and an experimental group (n = 24) receiving routine care along with the use of the Endotracheal Tube Adjustable Stabilizing Set, developed by the researchers. The latter set comprises an endotracheal tube-holding cap, head-locked pillows, and an oxygen meter. Data were analyzed using descriptive statistics, t-tests, chi-square tests, and Fisher's exact tests. Results show that the control group had an average tracheal tube insertion time of 78.94 hours, while the experimental group had an average of 39.35 hours. The incidence of unplanned extubation was 33.33% (8 cases) in the control group and 4.17% (1 case) in the experimental group. The unplanned extubation rate per 100 ventilator days was 4.41 times in the experimental group, significantly less than in the control group (23.84 times). The experimental group also exhibited significantly more time spent on vital signs and oxygen saturation within normal limits than the control group. In conclusion, using the Endotracheal Tube Adjustable Stabilizing Set in neonatal care can improve patient outcomes by reducing the incidence of unplanned extubation and stabilizing vital signs. This set has passed patentability evaluation for product design and enhances neonatal care by stabilizing endotracheal tubes, reducing slippage, and helping nurses provide more effective care. However, further testing in different settings with larger sample sizes and an equal average tracheal tube insertion time between the two groups is recommended to validate these findings.